2021
DOI: 10.1007/s11606-021-06931-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-identified Race and COVID-19-Associated Acute Kidney Injury and Inflammation: a Retrospective Cohort Study of Hospitalized Inner-City COVID-19 Patients

Abstract: Background Black individuals have been disproportionately affected by the coronavirus disease 2019 (COVID-19). However, it remains unclear whether there are any biological factors that predispose Black patients to COVID-19-related morbidity and mortality. Objective To compare in-hospital morbidity, mortality, and inflammatory marker levels between Black and White hospitalized COVID-19 patients. Design and Participants This single-center retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“… 36 Many studies show that cancer patients with COVID-19 in comparison to cancer patients without COVID-19 have a higher probability of mortality and are strongly recommended to adhere to preventive measures. 37 , 38 Therefore, more data is required to identify the severe outcomes between DM cancer patients with COVID-19 and those without the infection.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Many studies show that cancer patients with COVID-19 in comparison to cancer patients without COVID-19 have a higher probability of mortality and are strongly recommended to adhere to preventive measures. 37 , 38 Therefore, more data is required to identify the severe outcomes between DM cancer patients with COVID-19 and those without the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D modulates the immune system by suppressing the T helper 1 immune profile and upregulating the expression of regulatory T cells, thereby reducing the severity of cytokine storm. Therefore, vitamin D deficiency puts Black patients at a higher risk of cytokine storm and resulting systemic and intrarenal inflammation ( Charoenngam et al., 2021 ).…”
Section: Ethnic Differences In the Incidence Of Aki Among Patients With Covid-19mentioning
confidence: 99%
“…Charoenngam et al compared the hospital outcomes of Black and White hospitalized patients with COVID-19 at Boston Medical Center, the largest safety net hospital in New England. After adjusting for age, gender, BMI, potential type 2 diabetes, hypertension, and baseline estimated glomerular filtration rate (eGFR), the odds of AKI in black patients were statistically significantly higher (aOR 2.16, 95% CI, 1.57-2.97) (Charoenngam et al, 2021). In order to determine the risk factors related to the development of AKI in patients with COVID-19, Hirsch et al found that black race was both an independent risk factor and an independent predictor for the occurrence of AKI through multivariate analysis (Hirsch et al, 2020).…”
Section: Ethnic Differences In the Incidence Of Aki Among Patients Wi...mentioning
confidence: 99%
“…Table I details the study characteristics. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 These 11 studies included a total of 20,023 patients with a proportion of 27-54.2% of female patients. DVT and PE was a single outcome termed VTE in 5 studies and of those, a single study reported VTE and mortality as a composite primary outcome.…”
Section: Resultsmentioning
confidence: 99%